International Standardization in the Design of “Shore to Ship” - Power Supply Systems of Ships in Port - Tarnapowicz Dariusz; German-Galkin Sergiej (Management Systems in Production Engineering, 2018)
The decisive source of air pollution emissions in ports is the berthed ships. This is primarily caused by the work of ship’s autonomous generator sets. One way of reducing the air pollution emissions in ports is the supply of ships from electricity inland system. The main problem connected with the power connection of ships to the inland network is caused by different values of levels and frequencies of voltages in these networks (in various countries) in relation to different values of levels and frequencies of voltages present in the ship’s network. It is also important that the source power can range from a few hundred kW up to several MW. In order to realize a universal „Shore to Ship” system that allows the connection of ships to the electricity inland network, the international standardization is necessary. This article presents the current recommendations, standards and regulations for the design of „Shore to Ship” systems.